New Guinea has the world's richest island flora - Camara-Leret, Rodrigo; Frodin, David G.; Adema, Frits; Anderson, Christiane; Appelhans, Marc S.; Argent, George; Guerrero, Susana Arias; Ashton, Peter; Baker, William J.; Barfod, Anders S.; Barrington, David; Borosova, Renata; et al. (Nature Publishing Group, 2020)
New Guinea is the world's largest tropical island and has fascinated naturalists for centuries(1,2). Home to some of the best-preserved ecosystems on the planet(3)and to intact ecological gradients-from mangroves to tropical alpine grasslands-that are unmatched in the Asia-Pacific region(4,5), it is a globally recognized centre of biological and cultural diversity(6,7). So far, however, there has been no attempt to critically catalogue the entire vascular plant diversity of New Guinea. Here we present the first, to our knowledge, expert-verified checklist of the vascular plants of mainland New Guinea and surrounding islands. Our publicly available checklist includes 13,634 species (68% endemic), 1,742 genera and 264 families-suggesting that New Guinea is the most floristically diverse island in the world. Expert knowledge is essential for building checklists in the digital era: reliance on online taxonomic resources alone would have inflated species counts by 22%. Species discovery shows no sign of levelling off, and we discuss steps to accelerate botanical research in the 'Last Unknown'(8). A catalogue of the vascular flora of New Guinea indicates that this island is the most floristically diverse in the world, and that 68% of the species identified are endemic to New Guinea.